Facile separation and regeneration of LiFePO4 from spent lithium-ion batteries via effective pyrolysis and flotation: An economical and eco-friendly approach. (1st February 2023) - Zhong, Xuehu; Mao, Xiaohui; Qin, Wenqing; Zeng, Hongbo; Zhao, Guangjin; Han, Junwei
Graphical abstract: Highlights: Efficient separation and direct regeneration of spent LiFePO4 have been achieved. The first discharge capacity of the regenerated LiFePO4 is as high as 161.37 mAh/g. Selective adsorption of maize starch can enhance flotation of the anode material. The recycling process is efficient, low-cost, and environmentally friendly. Abstract: The facile recycling of spent lithium-ion batteries (LIBs) has attracted much attention because of its great significance to the environmental protection and resource utilization. Hydrometallurgical process is the most common method for recycling spent LIBs, but it is difficult to economically recover spent LiFePO4 batteries, because of the complicated metal separation process and low added value of its products. Herein, a novel and facile approach has been developed to achieve the direct regeneration of LiFePO4 from spent LIBs. By employing a flotation process after effective pyrolysis, it is found that 91.57% of LiFePO4 can be recovered from spent LIBs. Different surface hydrophobicity of cathode and anode active materials could be achieved via the selective adsorption of causticized soluble starch on the surfaces of spent LiFePO4, which effectively enhances the separation performance in flotation process. The recovered LiFePO4 barely contains metal impurities, which can be directly regenerated as new LiFePO4 materials with the first discharge capacity of 161.37 mAh/g, and their capacity retention is as high as 97.53% after 100 cycles at 0.2C. A technology assessment and economic evaluation indicate the developed regeneration approach of LiFePO4 is environmentally and economically feasible, which avoids the complex element separation process and achieves the facile recycling of spent LiFePO4 .